2023
DOI: 10.1002/jobm.202300250
|View full text |Cite
|
Sign up to set email alerts
|

The role of periodontitis‐associated bacteria in Alzheimer's disease: A narrative review

Abstract: Alzheimer's disease causes memory loss and dementia in older adults through a neurodegenerative mechanism. Despite the pathophysiological clarification of this cognitive disorder, novel molecular and cellular pathways should be identified to determine its exact mechanism. Alzheimer's disease (AD) is pathologically characterized by senile plaques comprising beta‐amyloid and neurofibrillary tangles (NFTs) formed by hyperphosphorylated tau as a microtubule‐associated protein with a key role in the pathogenesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 112 publications
0
4
0
Order By: Relevance
“…Paxillin plays a pivotal role in cell morphologic changes, cell motility, adhesion, migration, and cell signaling [52,53]. In addition, cell adhesion molecules play a role in adhesion and function as tumor suppressors [54]. Disorganized cell-cell or cell- In all the samples of all the study groups, the basal/peripheral layers demonstrated more prominent staining than the suprabasal layer.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Paxillin plays a pivotal role in cell morphologic changes, cell motility, adhesion, migration, and cell signaling [52,53]. In addition, cell adhesion molecules play a role in adhesion and function as tumor suppressors [54]. Disorganized cell-cell or cell- In all the samples of all the study groups, the basal/peripheral layers demonstrated more prominent staining than the suprabasal layer.…”
Section: Discussionmentioning
confidence: 95%
“…Paxillin plays a pivotal role in cell morphologic changes, cell motility, adhesion, migration, and cell signaling [52,53]. In addition, cell adhesion molecules play a role in adhesion and function as tumor suppressors [54]. Disorganized cell-cell or cell-extracellular matrix (ECM) attachment can significantly be provided towards unmanaged cell proliferation and progressive deformity of normal tissue construction [55].…”
Section: Discussionmentioning
confidence: 99%
“…Also, caspase-3 was observed in the cytoplasm of the epithelial cells, which could consequently facilitate the activity of BIRC6 [22]. In OLP, apoptosis is inhibited by several antiapoptotic factors [43,44]. Tobon et al indicated that the expression of caspase-3 was strong in basal epithelial cells and further suggested that caspase is active in the proliferating compartment of OLP lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that PBMT contributes to tissue regeneration by exerting biological modulatory effects on cell differentiation, improving the healing of fractures, regenerating periodontal tissue, promoting implant osseointegration, and facilitating bone reconstruction. 104,105 These effects have been observed both with and without the utilization of biomaterials. At the same time, research on the clinical practice of using PBMT to aid in healing after bone graft reconstruction surgery is limited; the bovine bone graft is frequently utilized as an alternative material in various reconstructive areas, such as traumatology, skeletal aging, facial prosthetic rehabilitation, craniomaxillary surgery, and esthetic aging.…”
Section: Bonementioning
confidence: 99%